Development of a high‐throughput genotoxicity assay using Umu test strains expressing human cytochrome P450s and NADPH‐P450 reductase and bacterial O‐acetyltransferase. (24th April 2017) - Hori, Hisako; Hirata, Daisuke; Fujii, Wataru; Oda, Yoshimitsu
Abstract : Umu test is one of the in vitro genotoxicity test that has been used widely. It was developed as a high‐throughput test system using the 96‐well microplate. We have previously constructed new umu test strains for the evaluation of genotoxicity of procarcinogenic metabolic products formed by cytochrome P450 (CYP) enzymes. In this study, a highly sensitive high‐throughput genotoxicity test was developed using four umu test strains (OY1002/1A1, OY1002/1B1, OY1002/1A2, and OY1002/3A4) that express human CYPs and NADPH‐P450 reductase. We found that the modified umu ‐microplate method was more sensitive than the conventional microplate method using strain OY1002/1A2. In addition, the new microplate method was better able to detect genotoxicity than the test tube method when the strain OY1002/1A2 was used and had similar sensitivity for the remaining three strains. When the microplate method was used, OY1002/1A2 showed stronger umuC gene expression in the presence of 2‐amino‐6‐methyldipyrido[1, 2‐ a :3', 2'‐ d ]imidazole, 2‐amino‐3‐methylimidazo[4, 5‐ f ]quinoline, 2‐amino‐3, 4‐dimethylimidazo[4, 5‐ f ]quinoline, 2‐amino‐3, 8‐dimethylimidazo[4, 5‐ f ]quinoxaline, 2‐aminofluorene, and 2‐aminoanthracene compared to other strains. We also confirmed CYP1A2 expression in OY1002/1A2 in this condition. These results indicate that the microplate version of this test system can detect the genotoxicity of heterocyclic and aromatic amines with high sensitivity and can be used for high‐throughput screening of potentially genotoxic compounds. Environ. Mol. Mutagen. 58:209–216, 2017. © 2017 Wiley Periodicals, Inc.